Common variable immunodeficiency with granulomatous‐lymphocytic interstitial lung disease treated with monoclonal antibodies against COVID‐19: A case report. Issue 1 (23rd January 2023) - Lechner, Christian; Zöggeler, Thomas; Bellmann, Romuald; Brunner, Jürgen; Zlamy, Manuela; Schirmer, Michael
Abstract: Common variable immunodeficiency (CVID) is the most prevalent primary immunodeficiency. We present a 22‐year‐old Caucasian woman with CVID and granulomatous lymphocytic interstitial lung disease who contracted COVID‐19 and was successfully treated with sotrovimab and molnupiravir. This treatment may have contributed to the relatively mild disease course of COVID‐19 in our patient. Abstract : The use of monoclonal antibodies directed against SARS‐CoV‐2 in combination with molnupiravir in a patient with CVID and GLILD is safe.